Additive effects of warming and grazing on fine-root decomposition and loss of nutrients in an alpine meadow. (13th March 2022) - Zhou, Yang; Lv, Wang-Wang; Wang, Shi-Ping; Zhang, Li-Rong; Sun, Jian-Ping; Jiang, Li-Li; Liu, Pei-Pei; Wang, Qi; Li, Bo-Wen; Wang, A; Hong, Huan; Zhang, Su-Ren; et al.
Abstract: Fine-root decomposition is a critical process regulating ecosystem carbon cycles and affecting nutrient cycling and soil fertility. However, whether interaction between warming and grazing affects fine-root decomposition is still under-researched in natural grasslands. A two-factorial experiment with asymmetric warming (i.e. daytime vs. nighttime and growing season vs. nongrowing season) and moderate grazing (i.e. about average 50% forage utilization rate) was conducted to explore whether warming and grazing affect fine-root decomposition and loss of nutrients during a 2-year decomposition period in an alpine meadow on the Tibetan Plateau. Both warming and grazing facilitated carbon cycling through increase in fine-root decomposition, and influenced element cycling which varies among elements. The effects of warming and grazing on fine-root decomposition and loss of nutrients were additive. Both warming and grazing significantly increased cumulative percentage mass loss and total organic carbon loss of fine roots during the 2-year experiment. Only warming with grazing treatment reduced percentage nitrogen loss, whereas warming, regardless of grazing, decreased percentage phosphorus loss. Warming and grazing alone increased percentage loss of potassium, sodium, calcium and magnesium compared with control. There were no interactions between warming and grazing on fine-root decomposition and loss of nutrients. There was greater temperature sensitivity of decreased phosphorus loss than that of decreased nitrogen loss. Different temperature sensitivities of percentage loss of nutrients from fine-root decomposition would alter ratios of the available nutrients in soils, and may further affect ecosystem structure and functions in future warming.